2021
DOI: 10.1007/s12264-021-00741-5
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Receptor Coactivator 3 Regulates Synaptic Plasticity and Hippocampus-dependent Memory

Abstract: Steroid hormones play important roles in brain development and function. The signaling of steroid hormones depends on the interaction between steroid receptors and their coactivators. Although the function of steroid receptor coactivators has been extensively studied in other tissues, their functions in the central nervous system are less well investigated. In this study, we addressed the function of steroid receptor coactivator 3 (SRC3) – a member of the p160 SRC protein family that is expressed predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“… 28 In previous studies, we demonstrated that SRC3‐mediated CaM acetylation was important for CaMKIIα activity and hippocampus‐dependent memory in mice. 31 , 45 , 46 Here, we showed that HDAC9‐mediated CaM deacetylation and CaMKIIα activity are severely abnormal in AD mouse brain. In addition to CaMKIIα, CaM has many other target proteins, several of which have been implicated in synaptic plasticity, neurotransmission or neuronal excitability.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“… 28 In previous studies, we demonstrated that SRC3‐mediated CaM acetylation was important for CaMKIIα activity and hippocampus‐dependent memory in mice. 31 , 45 , 46 Here, we showed that HDAC9‐mediated CaM deacetylation and CaMKIIα activity are severely abnormal in AD mouse brain. In addition to CaMKIIα, CaM has many other target proteins, several of which have been implicated in synaptic plasticity, neurotransmission or neuronal excitability.…”
Section: Discussionmentioning
confidence: 77%
“…While total CaM, CaMKIIα, GluR1, and PSD95 did not change significantly in WT and APP/PS1 mice (Figure 2A,E–H,J,N–Q). In previous studies, we identified that SRC3 was the CaM acetyltransferase, and revealed that CaM acetylation was necessary for CaMKIIα activation 31,45,46 . We studied whether decreased CaM acetylation is caused by reduced SRC3, and found that SRC3 did not change significantly in APP/PS1 mice, compared to WT mice (Figure 2A,I,J,R).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations